2018
DOI: 10.1016/j.coi.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Control of autoreactive B cells by IgM and IgD B cell receptors: maintaining a fine balance

Abstract: A substantial fraction of mature naïve B cells recognize endogenous antigens, and this autoreactivity must be controlled to prevent autoantibody secretion. Selective downregulation of the IgM BCR on autoreactive B cells has long been appreciated, and recent findings illustrate how this might impose tolerance. The BCR isotype maintained on autoreactive B cells, IgD, is less sensitive to endogenous antigens than IgM. This reduced sensitivity may be conferred by structural properties of IgD and/or differential as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Recently, it has been shown that secreted IgM regulates B cell development by acting as a decoy for self-antigen [ 47 ]. It also seems that surface expression of IgM plays an important role in the direction of B cell subset differentiation [ 38 , 52 ]; mice lacking secreted IgM displaying increased BCR signaling developed increased MZ and decreased FO B cell numbers [ 47 , 53 ]. In atherosclerosis, loss of secreted IgM results in accelerated lesion formation due to reduced levels of B cells expressing the low-affinity IgE receptor CD23 and elevated IgE synthesis [ 54 ].…”
Section: Bcr Signaling B Cell Development and Atherosclerosismentioning
confidence: 99%
“…Recently, it has been shown that secreted IgM regulates B cell development by acting as a decoy for self-antigen [ 47 ]. It also seems that surface expression of IgM plays an important role in the direction of B cell subset differentiation [ 38 , 52 ]; mice lacking secreted IgM displaying increased BCR signaling developed increased MZ and decreased FO B cell numbers [ 47 , 53 ]. In atherosclerosis, loss of secreted IgM results in accelerated lesion formation due to reduced levels of B cells expressing the low-affinity IgE receptor CD23 and elevated IgE synthesis [ 54 ].…”
Section: Bcr Signaling B Cell Development and Atherosclerosismentioning
confidence: 99%
“…Worth noting in biological systems function and homoeostasis depend on ne balance of molecules i.e. not necessarily the quantity [31,32]. However, using proteomic platform the identi ed PPs were selected based on quantity not function.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30,43 ] The unique structure of the IgD‐class BCR that mediates ignorance to monovalent antigen [ 42 ] and a nano‐cluster‐specific surface expression whilst pairing with distinct coreceptors [ 71,72 ] suggests a specialized role in B cell biology. [ 44,73,74 ]…”
Section: The Role Of the Igd‐class Bcr In Adaptive Tolerancementioning
confidence: 99%